2012
DOI: 10.3144/expresspolymlett.2012.16
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and melting behavior of nanoclay-containing polypropylene/poly(trimethylene terephthalate) blends

Abstract: This contribution concerns preparation and characterization of polypropylene (PP)/poly(trimethylene terephthalate) (PTT) melt-mixed blends in the presence of organically-modified montmorillonite nanoclays and functional compatibilizers. Immiscibility and nanocomposite formation were confirmed via transmission electron microscopy. An intercalated structure was observed by wide angle X-ray diffraction technique. Crystallization, and melting characteristics were studied by differential scanning calorimetry in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…If a comparison is made between blending recycled polymers with nanomaterials [7,8] some studies have found that a small load is sufficient to develop excellent properties without greatly increasing density and cost. It has been found that they have acted as a nuclear agent and accelerated the rate of crystallization of the polymer, increasing the melting resistance and viscosity of the polymers [9][10][11][12][13][14].The aim of this study is to develop, characterize and investigate, according to the filler content, blends of recycled PET with nano-silica and titanium oxide, in order to obtain materials used in the manufacture of parts used for design verification, shape verification, models for casting and medical application processes.…”
Section: Introductionmentioning
confidence: 99%
“…If a comparison is made between blending recycled polymers with nanomaterials [7,8] some studies have found that a small load is sufficient to develop excellent properties without greatly increasing density and cost. It has been found that they have acted as a nuclear agent and accelerated the rate of crystallization of the polymer, increasing the melting resistance and viscosity of the polymers [9][10][11][12][13][14].The aim of this study is to develop, characterize and investigate, according to the filler content, blends of recycled PET with nano-silica and titanium oxide, in order to obtain materials used in the manufacture of parts used for design verification, shape verification, models for casting and medical application processes.…”
Section: Introductionmentioning
confidence: 99%
“…33 Image given in Figure 5(e) for compatibilized reactions clearly indicates both the occurrence of exfoliation and intercalation, while the uncompatibilized image (Figure 5d) shows the intercalation of PB into the clay galleries. 34 …”
Section: Transmission Electron Microscope (Tem)mentioning
confidence: 99%
“…Several studies have shown that small amounts of well dispersed organoclays have the ability to act as effective nucleating agents, which accelerates the crystallization of the PP matrix and increases its crystallinity. 28,29 In the case of the blend nanocomposites, Figures 1 and Detailed regarding sample abbreviation can be found in Experimental section and Table I.…”
Section: Thermal Propertiesmentioning
confidence: 99%